OHVIRA Syndrome and Ureteral Ectopy Draining in the Ipsilateral Hemiuterus, Diagnosed in the Prepubertal Age Group: Case-Report and Literature Review - Teodora Telecan; Roxana Denisa Capras; Gabriela Adriana Filip; Emanuela Maria Ionutas; Dan Vasile Stanca; Carmen-Bianca Crivii (Medicina)
Background: Müllerian (paramesonephric) duct anomalies (MDA) are a rare condition, occurring in 5.5% of female newborns. One of the most complex malformations is represented by Obstructed Hemivagina and Ipsilateral Renal Anomalies (OHVIRA) syndrome, also known as Herlyn –Werner–Wunderlich (HWW) syndrome. Case presentation: We present the case of a 7-year-old asymptomatic premenarchal female patient diagnosed with OHVIRA syndrome with ipsilateral renal hypoplasia and ectopic ureteral implantation at the level of the uterus. As the patient developed urinary incontinence after the incision of the vaginal septum, right-sided 3D laparoscopic total nephrectomy was performed. Literature review: OHVIRA syndrome associated with ureteral ectopy is a rare occurrence, being encountered in 0.0064% of cases. The premenarchal diagnosis represents a challenge, due to the underdeveloped status of the genital tract. However, it should be ruled out in female newborns with unilateral renal agenesia or multicystic dysplastic kidney. Most reported cases describe the obstructed hemivagina as the site of ureteral ectopy. To our knowledge, this is the first reported case of OHVIRA syndrome with ectopic ureter draining at the level of the ipsilateral hemiuterus, diagnosed before the pubertal age. Conclusions: OHVIRA syndrome is one of the rarest Müllerian duct abnormalities. The management of these patients should be conducted in multidisciplinary teams, with long-term urological and gynecological follow-ups.